OP13 Molecular response to ustekinumab in moderate-to-severe ulcerative colitis by serum protein and biopsy gene expression analysis: Results from the UNIFI Phase 3 induction study. (25th January 2019) - Li, K; Yang, F; Hayden, K; Strawn, D; Wadman, E; Bhagat, S; Marano, C; Friedman, J R
Abstract: Background: The cytokines IL-12 and IL-23 are elevated in ulcerative colitis (UC) and genetic association suggests that they play causative roles in the disease. Ustekinumab (UST), an anti-IL-12p40 monoclonal antibody that blocks both cytokines, is an effective therapy for moderate-to-severe UC, but its molecular effects in UC patients remain unknown. Methods: Colonic biopsy mRNA and serum samples from the first 60% of patients who were randomised in the UNIFI Phase 3 induction study of UST in UC 1 were analysed, with equal representation of patients with a history of biological therapy failure (BF) and those without (BN) (Table 1). Biopsy and serum samples from healthy subjects were analysed as controls. Results: Colon biopsies from UC patients had a gene expression disease profile of 4095 probe sets, including genes involved in inflammatory response, tissue remodelling and wound healing, host–microbe interaction, intestinal permeability, and solute transport. BF and BN UC patients shared almost identical disease profiles. At Week 8 after UST induction therapy, the disease profile and top canonical pathways were significantly normalised in responders to UST. A smaller magnitude of normalisation was observed in responders to PBO. No significant change in disease signature occurred in non-responders. At baseline, BF and BN UC patients had similar serum profiles, with significantly elevated levels of IFN γ, IL-17A, IL-22, SAA, NGAL, MMPs, and TNF vs. healthy controls. Normalisation of IFN γ, SAA, IL-17A, and IL-22 was first detected in responders to UST at Week 4, the earliest time point in our assessment, and continued to improve through Week 8. A trend of normalisation of MMPs, IL-10, and NGAL was observed in UST responders; this trend was weaker or absent in UST non-responders and PBO-treated patients. TNF was elevated in UC prior to treatment and was not normalised by UST induction therapy. Conclusions: Transcriptomic and protein analyses in this subset of patients from the Phase 3 UC induction study demonstrated the suppression of IL-12 (IFN γ) and Il-23 (IL-17A) pathways and normalisation of the UC disease gene expression profile in response to UST. These results provide insight into the molecular mechanisms of UST efficacy. Reference 1. Sands BE, Sandborn WJ, Panaccione R, et al. Safety and efficacy of ustekinumab induction therapy in patients with moderate to severe ulcerative colitis: Results from the phase 3 UNIFI study. Oral Presentation at ACG, October 9, 2018, Philadelphia, PA.